THE ROLE OF COUNTER-PATRIARCHY MEDIA MUBADALAH.ID IN SUPPORTING THE ELIMINATION OF SEXUAL VIOLENCE BILL RATIFICATION - Khairani, Irma; Sadiyatunnimah, Siti; Djafar, T.B. Massa (Journal of Social Political Sciences, 2021)
The draft on the Elimination of Sexual Violence Law is one of the bills that has been discussed for a long time in indonesia. Various views of the relevant parties were discussed quite a lot in media, both for and againts the bill. Mubadalah.id is a counter-patriarchal media which is one of the instruments and strategies used by women’s movement in Indonesia expressing the importance of ratifying the bill. This study examines the role of Mubadalah.id as a counter-patriarchal media which express the urgency of this ratification. In order to explain the problems, this research has used a descriptive qualitative research method that relies on in-depth interviews with key resources related to the ratification of this bill. Literatur reviews have been carried out to obtain supporting data that will confirm the data from previous interviews. The findings show that Mubadalah.id has a role as a political communication tool for the women’s movement in Indonesia in supporting the ratification of the bill through several strategies: channeling messages regarding the urgency of the passage of the bill; countering the narratives that reject the ratification of the bill; encourage the ratification of the bill by forming opinions supporting the ratification.